High‐Energy (>10 MeV) Oxygen and Sulfur Ions Observed at Jupiter From Pulse Width Measurements of the JEDI Sensors. Issue 20 (28th October 2019) - Westlake, J. H.; Clark, G.; Haggerty, D. K.; Jaskulek, S. E.; Kollmann, P.; Mauk, B. H.; Mitchell, D. G.; Nelson, K. S.; Paranicas, C. P.; Rymer, A. M.
Abstract: The Jovian polar regions produce X‐rays that are characteristic of very energetic oxygen and sulfur that become highly charged on precipitating into Jupiter's upper atmosphere. Juno has traversed the polar regions above where these energetic ions are expected to be precipitating revealing a complex composition and energy structure. Energetic ions are likely to drive the characteristic X‐rays observed at Jupiter (Haggerty et al., 2017, https://doi.org/10.1002/2017GL072866 ; Houston et al., 2018, https://doi.org/10.1002/2017JA024872 ; Kharchenko et al., 2006, https://doi.org/10.1029/2006GL026039 ). Motivated by the science of X‐ray generation, we describe here Juno Jupiter Energetic Particle Detector Instrument (JEDI) measurements of ions above 1 MeV and demonstrate the capability of measuring oxygen and sulfur ions with energies up to 100 MeV. We detail the process of retrieving ion fluxes from pulse width data on instruments like JEDI (called "puck's"; Clark, Cohen, et al., 2016, https://doi.org/10.1002/2017GL074366 ; Clark, Mauk, et al., 2016, https://doi.org/10.1002/2015JA022257 ; Mauk et al., 2013, https://doi.org/10.1007/s11214‐013‐0025‐3 ) as well as details on retrieving very energetic particles (>20 MeV) above which the pulse width also saturates. Plain Language Summary: The Juno mission has observed high‐energy, heavy ions of the sort that are thought to be responsible for X‐Rays from Jupiter's poles. These heavy ions originate from Jupiter's volcanic moon Io and eventually precipitate into and interact with Jupiter's atmosphere resulting in X‐Ray emission. Key Points: The Juno JEDI instrument is shown to have the unplanned capability to measure heavy ions to energies as high as 100 MeV As such, the JEDI instrument has the capability to measure those ions needed to generate polar X‐rays at Jupiter (greater than tens of megaelectron volts O and/or S) Although not yet directly correlated with polar X‐rays, we show that heavy ions up to 100 MeV are indeed observed over Jupiter's polar regions